The Effectiveness Of Simulation Exercises (E.G., Tabletop, Field) In Improving Health Security Response Capabilities: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Simulation exercises, including tabletop and field-based simulations, are widely used to strengthen health security preparedness and response systems. These exercises are intended to test emergency plans, enhance coordination, and improve decision-making across public health, healthcare, and emergency management sectors. However, the effectiveness of such exercises in improving health security response capabilities has not been consistently synthesized.Objectives: This systematic review aims to assess the effectiveness of simulation exercises in enhancing health security preparedness and response capabilities, with particular focus on system performance, interagency coordination, operational readiness, and identification of response gaps during public health emergencies.Methods: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Electronic databases including PubMed, Embase, Scopus, and Web of Science were searched for studies evaluating tabletop and field simulation exercises related to health security. Eligible studies underwent independent screening, data extraction, and quality appraisal. Due to heterogeneity in study designs and outcome measures, a narrative synthesis was performed.Results: A total of 1,247 records were identified, of which 38 studies met the inclusion criteria and were included in the final synthesis. The majority of studies reported improvements in participants’ knowledge, role clarity, communication, and adherence to emergency protocols following simulation exercises. Tabletop exercises were particularly effective in strengthening strategic planning, policy understanding, and decision-making processes, while field exercises demonstrated greater impact on operational readiness, logistics coordination, and interagency collaboration. Most studies highlighted the value of simulations in identifying system-level gaps and testing surge capacity; however, outcome measures were often subjective, and few studies included longitudinal follow-up or objective performance indicators.Conclusion: Simulation exercises are effective tools for enhancing health security response capabilities, particularly when used as part of a comprehensive preparedness strategy. Both tabletop and field exercises offer complementary benefits. Nevertheless, the evidence base is limited by methodological variability and inconsistent evaluation frameworks. Future research should emphasize standardized outcome measures and rigorous study designs to better quantify the impact of simulation exercises on health security preparedness.